Aspect-Oriented Software Development in Practice: tales from AOSD-Europe. - Rashid, Awais; Cottenier, Thomas; Greenwood, Phil; Chitchyan, Ruzanna; Meunier, Regine; Coelho, Roberta; Südholt, Mario; Joosen, Wouter (Computer (00189162), 2010)
The article analyzes several medium- and large-scale projects employing aspect-oriented software development (AOSD) techniques. It cites the reasons why advanced AO features and new tool and language prototypes are mainly used in industry-academic pilots or controlled laboratory experiments. It mentions the approach that should be taken by organizations to promote smooth adoption of AOSD techniques. It explores the potential pitfalls of AOSD techniques.